Temporal associations of life with solar and geophysical activity - T. K. Breus; G. Cornélissen; F. Halberg; A. E. Levitin (Annales Geophysicae)
In biology, circadian rhythms with a period of one cycle in 20–28 h are known to be ubiquitous and partly endogenous. Rhythms with a frequency lower than one cycle per day are called 'infradian rhythms'. Among them are components with one cycle in about 3.5, 7, 14 and 28 days, the multiseptans, which, like the circadians, must be regarded as a general characteristic of life: they characterize unicells as well as much more differentiated organisms. We hypothesize that heliogeophysical factors other than the solar visible light, held responsible for the evolution of circadian periodicity, underlie the infradian rhythms of biosystems. The periodicities in the solar wind and variations in the interplanetary magnetic field (IMF) which are associated with the solar rotation are very similar in length to the biological periodicities. We investigate the temporal relations of variations in solar activity and in biological systems to test associations between events in the IMF, in geomagnetic disturbance, in myocardial infarction and in physiology. By cross-spectral analysis, we also find relations at certain frequencies between changes in human physiology on the one hand, and (1) the vertical component of the induction vector of the IMF, Bz, and (2) a global index of geomagnetic disturbance, Kp, on the other hand. We wish to stimulate interest in these periodicities of both biological systems and geophysical endpoints among physicists and biologists alike, so that problems relevant to clinicians and other biologists, including evolutionists, are eventually solved by their cooperation with the geophysical community.